Subjective longevity in Latin America: the cases of Chile and Mexico - NOVAK, Beatriz; LOZANO-KEYMOLEN, Daniel (Papeles de Población, 2016)
The body of research on subjective survival expectations in developing countries is scant and to the best of our knowledge in Latin America is virtually non-existent. The main objective of this study is to investigate and compare the determinants of subjective survival expectations as they are stated by individuals aged 65 and over in Chile and Mexico. The determinants of subjective survival probabilities are studied by means of linear regression analysis and life expectancies are estimated by means of non-linear regression methods. Results show that the determinants of subjective survival expectations are consistent for both, Chile and Mexico, with those reported by the literature for the US and Europe. However, there are important differences between survival probabilities and life expectancies mainly based on the more pessimistic view of their future survival that Mexican older adults show compared with Chileans.